PERAN LITERASI KEUANGAN DALAM PENGELOLAAN KEUANGAN MAHASISWA: indonesia - Adi Waluyo, Fikqi Indra; Marlina, Maria Asumpta Evi (Media Akuntansi dan Perpajakan Indonesia, 2020)
The purpose of this study is to explore the role of financial literacy for students in managing their finances. This research is based on data that shows student financial literacy in an accounting class is still low. The research method used in this research is descriptive qualitative method. This research conducted in an accounting study program at a university that based on entrepreneurship learning. Participants in this study were students in the fifth semester who met the criteria in the research. Data collection conducted by interviewing four students who met the criteria. The results of this study indicate that financial literacy plays a role for students in managing their finances. The role show in several stages. These stages are the stages of determining the source of funds, the stage of use of funds, the stage of risk management, and the future planning stage. Another finding in this study was that the existence of technology and education became the supporting students in implementing financial literacy.